Workflow for automatic renal perfusion quantification using ASL‐MRI and machine learning - Bones, Isabell K.; Bos, Clemens; Moonen, Chrit; Hendrikse, Jeroen; Stralen, Marijn (Magnetic resonance in medicine, 2022)
Purpose Clinical applicability of renal arterial spin labeling (ASL) MRI is hampered because of time consuming and observer dependent post‐processing, including manual segmentation of the cortex to obtain cortical renal blood flow (RBF). Machine learning has proven its value in medical image segmentation, including the kidneys. This study presents a fully automatic workflow for renal cortex perfusion quantification by including machine learning‐based segmentation. Methods Fully automatic workflow was achieved by construction of a cascade of 3 U‐nets to replace manual segmentation in ASL quantification. All 1.5T ASL‐MRI data, including M0, T1, and ASL label‐control images, from 10 healthy volunteers was used for training (dataset 1). Trained cascade performance was validated on 4 additional volunteers (dataset 2). Manual segmentations were generated by 2 observers, yielding reference and second observer segmentations. To validate the intended use of the automatic segmentations, manual and automatic RBF values in mL/min/100 g were compared. Results Good agreement was found between automatic and manual segmentations on dataset 1 (dice score = 0.78 ± 0.04), which was in line with inter‐observer variability (dice score = 0.77 ± 0.02). Good agreement was confirmed on dataset 2 (dice score = 0.75 ± 0.03). Moreover, similar cortical RBF was obtained with automatic or manual segmentations, on average and at subject level; with 211 ± 31 mL/min/100 g and 208 ± 31 mL/min/100 g (P < .05), respectively, with narrow limits of agreement at −11 and 4.6 mL/min/100 g. RBF accuracy with automated segmentations was confirmed on dataset 2. Conclusion Our proposed method automates ASL quantification without compromising RBF accuracy. With quick processing and without observer dependence, renal ASL‐MRI is more attractive for clinical application as well as for longitudinal and multi‐center studies.